2021
DOI: 10.1111/ijcp.14081
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic misuse and compliance with infection control measures during COVID‐19 pandemic in community pharmacies in Egypt

Abstract: Background Globally, antibiotics misuse by the public has been reported in the era of COVID‐19, despite the discouraging instructions of the World Health Organization, especially for mild cases. Objective Is to describe this antibiotic misuse and its contributing factors. Also, to measure the pharmacists' application of infection preventive practices during the pandemic. Methods A cross‐sectional study was conducted among randomly selected Egyptian community pharmacists (Center, East, Delta, and Upper Egypt) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 27 publications
2
48
1
Order By: Relevance
“…Yet, this study finding is much lower than 47% among the suspected COVID-19 cases reported in a previous hospital-based study from Bangladesh [ 20 ]. The proportion of antibiotics used for COVID-19 respondents in our study is also much lower than the study conducted in Egypt during the COVID-19 pandemic [ 17 ]. This may be likely to the fact that a very low number of COVID-19 cases were detected through this survey.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Yet, this study finding is much lower than 47% among the suspected COVID-19 cases reported in a previous hospital-based study from Bangladesh [ 20 ]. The proportion of antibiotics used for COVID-19 respondents in our study is also much lower than the study conducted in Egypt during the COVID-19 pandemic [ 17 ]. This may be likely to the fact that a very low number of COVID-19 cases were detected through this survey.…”
Section: Discussioncontrasting
confidence: 59%
“…Still, 49% of the respondents reported that antibiotics were effective against bacterial infection only [ 16 ]. Dispensing of antibiotics was increased profoundly in Egypt during the early period of the COVID-19 pandemic without proper clinical evaluation, and azithromycin, ceftriaxone, and linezolid were the major antibiotics used [ 17 ]. Approximately, 93% of the presumptive COVID-19 patients received antibiotics with official prescriptions and without prescriptions, of which 18% comprised of pharmacist and patient’s recommendations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Abuse of Antibiotics has been reported to be a key factor in worsening/aggravating the diseased condition in COVID-19 patients [2082,2083,2084,2085].…”
Section: Abuse Of Antibioticsmentioning
confidence: 99%
“…AMR represents a threat to sustainable development, leading to 11 million deaths annually [1,2]. The recent COVID-19 pandemic resulted in a significant increase in antibiotic sales [3] and extensive antibiotic use without proper clinical indication [4]. Hence, the overuse of antibiotics lays the foundations for further resistome propagation and multi-resistance evolution.…”
Section: Introductionmentioning
confidence: 99%